Secondary sclerosing cholangitis: an unusual presentation of leptospirosis - Tilan Aponso; W. M. D. A. S. Wanninayake; I. P. Wijesinghe; Nethma Jayasekara; Waruna Iddamalgoda; W. M. M. A. Wanasinghe (Tropical Medicine and Health)
Abstract Sclerosing cholangitis is a rare progressive cholestatic disease that is classified as secondary sclerosing cholangitis when it is caused by an identifiable cause. Sclerosing cholangitis has been linked to infections like COVID-19 and parasitic infections like Clonorchis sinensis and Ascaris lumbricoides. However, leptospirosis has not been linked to sclerosing cholangitis in the medical literature. In this article, we report a 37-year-old gentleman who was diagnosed with leptospirosis, worsened by painless cholestasis, while he was improving from leptospirosis. Magnetic resonance cholangiopancreatography revealed multiple short-segment biliary strictures, segmental dilatation, and mural irregularities in both intrahepatic ducts confirming the diagnosis of sclerosing cholangitis. After ruling out other potential causes and considering the initial presentation during a leptospirosis infection, we concluded that leptospirosis caused secondary sclerosing cholangitis. We report this as the first case of secondary sclerosing cholangitis in a leptospirosis patient without renal, respiratory, or cardiac complications, emphasizing the importance of ruling out this cause in a leptospirosis patient with persistent cholestasis.